Kondisi Terumbu Karang Diving Point Lekuan Dua Pulau Bunaken Sulawesi Utara - Gumolili, Youdy Joseph Hendrik; Karauwan, Maykel A.J.; Rondonuwu, Diana; Tangian, Diane (HOSPITALITI DAN PARIWISATA, 2023)
This research was carried out in coral reef area at diving point Lekuan 2 in May 28th 2022 by using the Line Intercept Transect cencus method on 5 m and 10 m depth. The aims of this research is to know the coral reef condition at dive point Lekuan 2 and to know the domination index of coral reef in Lekuan 2 Dive point. The results showed that the coral ref condition at dive point Lekuan 2 were good category (58,19%) with low coral diversity index (2,41), moderate community stability and low coral dominance index.